Toll-like receptor 4/nuclear factor-kappa B pathway is involved in activating microphages by polysaccharides isolated from Fagopyrum esculentum. Issue 1 (1st January 2019) - Chen, Zhen; Yu, Leilei; Cai, Xiaoniao; Ye, Fangpeng; Jin, Peisheng
ABSTRACT: Buckwheat polysaccharide fractions (BPFs) isolated from seeds of Fagopyrum esculentum have shown extensive immunomodulatory activities including activation of immune system. In this study, the immuno-modulation effects of BPFs on microphages were investigated. The obtained results show that BPFs can activate microphages as indicated by significant increases in the activity of inducible nitric oxide synthase (12.6 ± 1.30 U/mg prot), nuclear factor-kappa B (NF-κB) protein levels, and secretion of nitric oxide (NO) (21.5 ± 1.20 μmol/ml) and tumor necrosis factor-alpha (TNF-α) (71.2 ± 18.20 pg/ml). Moreover, blocking toll-like receptor 4 (TLR4)/NF-κB pathway using a specific antibody to TLR4 or inhibitor of NF-κB led to the significant inhibitory immuno-modulation effect on microphages as indicated by the decrease in the secretion level of NO and TNF-α. It is demonstrated that BPFs can activate microphages and TLR4/NF-κB pathway is involved in the induction of NO and TNF-α in macrophages by BPFs. Graphical abstract: uf0001 ● BPFs were found capable of activating macrophages. ● BPFs increase the NO and TNF-α secretion of macrophages. ● Toll-like receptor 4 (TLR4)/NF-κB pathway is involved in the activation process.